Knowledge of Mothers about Children Nutrition under Five Years in Babylon City, Iraq - Mazin faeq Abdulzahra,; Jabbar Taresh Ahmed,; Qais Ismaeel Kadhem, (University of Thi-Qar Journal of Science, 2023)
The study aims to identify mothers' knowledge about children's nutrition under five years in Babylon city. Materials and methods: This study is a cross-sectional study on mothers' knowledge about children's nutrition under five years in primary health care centers in urban and rural of Al- Hilla city. The study period runs from November 1st, 2021, to March 1st, 2022. The data was collected by questionnaire through questions and an interview with mothers after obtaining their approval. Results: shows the total knowledge score of mothers, most of them (54.3%) scored moderate knowledge, followed by (43.9%) scored good knowledge. Conclusion: the study reveals that it did not find a statistically important association between demographic characteristics and total knowledge score, except for age groups, house type, and educational level of mother and father. Aims of the study: To identify mothers' knowledge about children's nutrition under five years in Al-Hilla city, To find an association between total knowledge score and demographic characteristics.Keywords